Age at Menarche among the School Going Children of Jorpati, Kathmandu - Chalise, Usha; Pradhan, Allin; Lama, Chhiring Palmu; Panta, Prem Prasad; Dhungel, Shaligram (Journal of College of Medical Sciences-Nepal, 2018)
Background and objectives: The present study was conducted to explore the mean age at menarche and associating factors among the Nepali school girls of Jorpati, Kathmandu. Materials and methods: The 500 girls of aged between 9-18 years were collected from the seven school of Gokarneshowr Municipality, Jorpati, Kathmandu after taking ethical clearance from NHRC. The healthy girls without any growth-related disorders and genetic abnormalities were included in the study. The consent was taken from the school authority and individual student by providing written consent and ascent form. The data thus collected were tabulated and analyzed by using SPSS 16. Results: The age at menarche of the respondents was 12.56 ±1.12years and menarchial age varied from 9-16 years. Similarly, the mean age at menarche of sisters and mothers were 12.96 ± 1.25 and 14.30 ± 1.58 respectively. The mean age at menarche of vegetarian group was 12.42 years as compared to non-vegetarian was 12.58 years. The lowest mean age at menarche was in Newar (12.30 years) and highest mean age at menarche in Limbu (13.33years). Followed by age at menarche in Brahmin (12.58 years), Chhetri (12.74 years), Rai (12.60 years), Lama (12.43 years), Gurung (12.66 years) and others (12.56 years). Conclusions: There was decrease in age at menarche with successive generation as a result of increase in urbanization, better dwelling and smaller family size as compared to previous generation.